Influence of the COVID‐19 outbreak on transportation of pregnant women in an emergency medical service system: Population‐based, ORION registry. Issue 2 (23rd February 2022) - Ota, Koshi; Nishioka, Daisuke; Katayama, Yusuke; Kitamura, Tetsuhisa; Masui, Jun; Ota, Kanna; Nitta, Masahiko; Matsuoka, Tetsuya; Takasu, Akira
Abstract: Background: The coronavirus disease 2019 (COVID‐19), caused by Severe Acute Respiratory Syndrome Coronavirus 2, has spread rapidly across the world. Objective: To assess the influence of the COVID‐19 pandemic on the emergency medical service (EMS) for transportation of pregnant women by ambulance. Methods: This study was a retrospective, descriptive study using the Osaka Emergency Information Research Intelligent Operation Network system, and included pregnant women transported by ambulance in Osaka Prefecture between January 1, 2018 and December 31, 2020. The main outcome of the study was difficulty in obtaining hospital acceptance for transfer of patients (difficult‐to‐transfer cases). We calculated the rates of difficult‐to‐transfer cases using univariate and multivariate analyses. Results: Of the 1 346 457 total patients transported to hospitals by ambulance in Osaka Prefecture during the study period, pregnant women accounted for 2586 (909, 943, and 734, in 2018, 2019, and 2020, respectively). Logistic regression analysis revealed that pregnant women were negatively associated with difficult‐to‐transfer cases (adjusted OR 0.36, 95% CI 0.26–0.50). Compared with 2018, 2020 was significantly associated with difficult‐to‐transfer cases (adjusted OR 1.27, 95% CI 1.24–1.30). Conclusion: Pregnant women were consistently associated with reduced odds for being difficult‐to‐transfer cases. The COVID‐19 pandemic might have influenced difficult‐to‐transfer cases in 2020. Abstract : This study showed that pregnancy was consistently associated with reduced odds for difficult‐to‐transfer cases in 2020 even during the COVID‐19 outbreak.